A Tale of Two Imperial Residences: Aurangzeb’s Architectural Patronage - Sohoni, Pushkar (Journal of Islamic Architecture, 2016)
While the Mughal Emperor Aurangzeb Alamgir is not well-known for his architectural commissions as his predecessors, there are still a few extant buildings associated with him. Two of these are residential sites, built almost fifty years apart, at the beginning and end of his career as an emperor. This essay examines these hitherto unpublished sites, and documents them as part of a Mughal legacy in the Deccan that has remained uncelebrated. The palace at Aurangabad and a royal residential compound just outside of Ahmadnagar are the two sites which bracket the emperor’s career and offer an insight into his political fortunes and religious life as it changed.